The validation of Bahasa Malaysia translated OSDI - Badarudin, Noor Ezailina; Awang Abd Rahman, Aziimah; Ariffin, Azrin Esmady; Che Azemin, Mohd Zulfaezal; Ahmad, Norsham (Faculty of Medicine, University of Malaya, 2017)
Introduction: Dry eye disease (DED) is a multifactorial condition that results in symptoms of discomfort, visual disturbance and tear film instability with potential damage to the ocular surface. Symptoms are important in confirming the diagnosis. Questionnaire application is efficient in assessing symptoms of DED. Ocular Surface Disease Index (OSDI) questionnaire is a standard measure for DED used worldwide. The English version of OSDI may not be fully understood by the Malaysian population who communicate in Bahasa Malaysia. This study involves the translation and validation of the Bahasa Malaysia version of OSDI. Objective: To validate the same structure of OSDI in Bahasa Malaysia, to remove language barrier in assessing the DED. Methodology: Translation process was conducted via five phases; forward translation, synthesis of translation, backward translation, refine of translation and translation scrutinization. The result from translation process was transformed into an online questionnaire using JotForm program. It was distributed to 230 bilingual participants to answer both English and Bahasa Malaysia version. The responses were automatically calculated and replied via online. SPSS software was used to analyse the results, using Cronbach‟s alpha coefficients test to determine the reliability of the translated version. Result: The reliability of the scores of all items in OSDI-Bahasa were satisfactory with the Cronbach‟s Alpha ranging from the acceptable values of 0.88 to 0.94. No significant difference in the items, total score and OSDI score between the repeats of the OSDI-Bahasa (P>0.05) Conclusion. OSDI in Bahasa Malaysia is valid as an instrument to assess symptoms of DED.